COVID-19 and global food security: Two years later - McDermott, John J.; Swinnen, Johan (International Food Policy Research Institute, 2022)
Two years after the onset of the COVID-19 pandemic, the health, economic, and social disruptions caused by this global crisis continue to evolve. The impacts of the pandemic are likely to endure for years to come, with poor, marginalized, and vulnerable groups the most affected.